2020
DOI: 10.1111/tid.13447
|View full text |Cite
|
Sign up to set email alerts
|

Talaromycosis in a renal transplant recipient returning from South China

Abstract: Talaromycosis is a fungal infection endemic in Southeast Asia. We report a case of a renal transplant recipient who developed infection after a trip to South China. She presented with constitutional symptoms and was found to have an FDG‐avid lung mass. Histopathology demonstrated small yeast cells and culture grew Talaromyces marneffei. The patient was treated with 2 weeks of liposomal amphotericin B followed by itraconazole. The dose of tacrolimus was significantly reduced because of the interaction with itra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Of these, 4 included a review of related literature [ 2–4 , 198 ], 15 were cohort studies [ 10 , 32 , 47 , 53 , 54 , 56 , 57 , 62 , 63 , 71 , 89 , 100 , 184 , 185 , 187 ], and the majority were case reports. After careful review of references, 1 cohort [ 1 ] and 42 additional case reports or series were identified [ 199–213 ] including 20 [ 188 , 190 , 192 , 214–230 ] from a prior review [ 4 ]. ( Supplementary Material, Appendix 1 ; Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 4 included a review of related literature [ 2–4 , 198 ], 15 were cohort studies [ 10 , 32 , 47 , 53 , 54 , 56 , 57 , 62 , 63 , 71 , 89 , 100 , 184 , 185 , 187 ], and the majority were case reports. After careful review of references, 1 cohort [ 1 ] and 42 additional case reports or series were identified [ 199–213 ] including 20 [ 188 , 190 , 192 , 214–230 ] from a prior review [ 4 ]. ( Supplementary Material, Appendix 1 ; Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 268 SOT recipients with an endemic mycoses were described in 204 reports [ 4–8 , 13 , 16 , 18 , 20 , 21 , 23 , 25 , 27 , 28 , 33–37 , 40 , 42 , 45 , 46 , 48–52 , 55 , 58–61 , 64–70 , 72–88 , 90–99 , 101–146 , 148–168 , 170–183 , 186 , 188–197 , 207 , 209–244 ]. Table 1 summarizes their characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 55/M Guangxi, China kidney fever and shortness of breath After admission: Tac, MMF and prednisolone were discontinued; Methylpred (80 mg qd) Voriconazole Died 51/M Sichuan, China kidney coughing, hemoptysis After admission: MMF (0.5 g bid); Tac (1.0 mg bid) Oral posaconazole (400 mg bid) Cured Lang Q, et al [ 37 ], 2020. 53/F England kidney coughing, green sputum MMF was discontinued; Tac dose was reduced Liposomal amphotericin B daily for 2 weeks; oral itraconazole twice daily for 6 months Cured Vergidis P. et al [ 38 ], 2021. Ma W, et al [ 39 ], 2018.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…We searched literatures in the Web of Science and PubMed databases based on “ Talaromyces marneffei ”, “ Penicillium marneffei ”, “kidney transplantation”, and “renal transplantation”, which had been published up to October 2022. A total of 10 officially published papers reporting 11 cases of T. marneffei infection after kidney transplantation were retrieved ( Wang et al., 2003 ; Chan et al., 2004 ; Lin et al., 2010 ; Hart et al., 2012 ; Peng et al., 2017 ; Lang et al., 2020 ; Vergidis et al., 2021 ; Gupta et al., 2022 ; Li et al., 2022 ; Xing et al., 2022 ) ( Table 1 ). The above 11 recipients were summarized in order to enhance the cognition of T. marneffei infection after renal transplantation and improve the prognosis.…”
Section: Discussionmentioning
confidence: 99%